Planning scope and time in ERP projects - Necas, Josef (My University, 2018)
ERP systems have become a vital part of well-functioning businesses, ranging from SMEs to large businesses. Despite the name having a highly technical connotation, ERP projects are, by their nature, cross-dimensional and require both business and IT domains to work closely in order to achieve the project’s success. This study offers a practical, down-to-earth view of an ERP project with particular emphasis on the project planning of scope and time. Planning of scope and time is a crucial issue not only in ERP projects, but in projects in general. The case study offers insight into a real-life project with particularly extensive scope where correct scope and time planning were a crucial part of the project’s success. Tools and methodologies employed in the project’s scope and time planning were examined through qualitative research, leveraging knowledge of multiple highly experienced professionals, thus allowing for deep levels of practical insight into the complex issue of ERP projects planning.
Keywords: project management; project planning; ERP (enterprise resource planning); scope planning; time planning; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|